An Anisotropic Metamaterial Cover Layer for Scan Range Enhancement of Patch-Antenna Phased Arrays in Both Principal Planes - Mohammad Soltani; George V. Eleftheriades (IEEE Open Journal of Antennas and Propagation)
This work introduces a metamaterial cover layer designed to extend the scan range of patch-antenna phased arrays in both principal planes without compromising directivity. The key innovation lies in the anisotropic properties of the cover layer which suppress the excitation of the fundamental surface-wave (SW) mode, effectively mitigating scan blindness within the desired angular range. This suppression mechanism is simply not possible with a conventional dielectric-slab wide-angle impedance matching (WAIM) layer. The anisotropic slab SW suppression key mechanism is analyzed using the transverse resonance technique, yielding design equations for practical implementation. The metamaterial cover uniquely combines a wire medium (WM) slab and an artificial dielectric layer. This combination addresses two critical limitations of wide-angle scanning phased arrays: scan blindness and mutual coupling. The performance of the metamaterial cover is analyzed using the current sheet model and the spectral domain Green’s function of the stratified dielectric media, incorporating a detailed model of the WM slab. Results demonstrate an improvement in scan range across more than 10% fractional bandwidth. To validate the concept, a prototype is fabricated and applied to a home-made $8× 8$ -element patch-antenna phased array with half-wavelength element spacing and a limited scan range. Crucially, in the E-plane, where surface waves limit performance in the bare array, the scan range is dramatically increased from ±30° to ±50°. The prototype achieves a final scan range of ±50° in the E-plane and ±60° in the H-plane, experimentally confirming the effectiveness of the proposed metamaterial cover in enabling wide-angle scanning.